The importance of organizational climate for psychosocial safety in the prevention of sexual harassment at work - Malvin Ping Chieng Tan; Sharon Sam Mee Kwan; Azizi Yahaya; Ismail Maakip; Peter Voo Su Kiong (John Wiley & Sons Australia, Ltd, 2020)
Workplace sexual harassment is a prominent issue in Malaysia. Although the subject of sexual harassment has been researched for over two decades, information on how organizations could effectively prevent workplace sexual harassment is limited. The researchers investigated the importance of organizational climate for psychosocial safety of workplace sexual harassment prevention. Purposive random sampling was utilized to recruit participants in the study. Semi-structured interviews were then conducted with Malaysian employees (N = 20) from various organizations. The study applied the Grounded Theory Approach (Glaser & Strauss, 1976) to identify the participants' coping strategies in dealing with sexual harassment that occurred at their workplace. The interviews revealed that both genders were potential victims or witnesses of workplace sexual harassment. Since many Malaysian organizations do not implement any workplace sexual harassment prevention, most of the victims and witnesses tend to use passive self-coping approaches. Typically, policy and guidelines implementation would encourage employees to voice their concerns; however, we discovered that participants' motivation to use active coping strategies depended on organizational role rather than the policy and guidelines implementation. Surprisingly, we also found out that participants from zero policy organizations used active coping strategies when the sexual harassment reached intolerable levels. Organizations play a critical role in helping and supporting both victims and witnesses deal with sexual harassment at the workplace. Organizational climate for psychosocial safety is therefore crucial in the primary and secondary prevention of sexual harassment at work.